POTENSI TANAMAN OBAT INDONESIA ATASI TUMOR DAN KANKER: TINJAUAN SISTEMATIS: The Potential of Indonesian Medicinal Plants to Overcome Tumors and Cancer: A Systematic Review - Yusnita Julyarni Akri (Forind Press, 2024)
Indonesia with very high biodiversity has great potential for the development of drugs from natural products. The use of traditional medicine in treatment efforts continues to increase, the design of this study is a systematic review. The search for the articles discussed in this study uses several databases, including Pubmed, Proquest, and ScienceDirect, with a time span of 2014 to 2024. The keywords used to search for the article are medicinal plants, tumors, cancer, and anticancer. The type of article used is a research article. The collected articles are then re-selected using inclusion criteria, namely: 1) the purpose of the article is to analyze the potential of medicinal plants as anticancer, 2) it is an experimental research, and the exclusion criteria, namely 1) it is not a full-text article, 2) the article does not use Indonesian or English. Based on the 6 selected articles, there are several plants that have the potential to cure cancer. These plants have been scientifically tested to have active compounds that can kill cancer cells.